USM-UNIKAMA INDONESIA AGREES ON ENHANCING WORK COLLABORATIONS - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 27 February 2016 – The ViceChancellor of Universiti Sains Malaysia (USM), Professor Dato' Dr. Omar Osman recently received a courtesy visit by the delegation from Universitas Kanjuruhan Malang, Indonesia (UNIKAMA), led by its Rector, Dr. Pieter Sahertian at the USM Chancellory Conference Room.